RELAKSASI UMKM DIMASA COVID-19 MELALUI PERBANKAN SYARIAH DI KABUPATEN SUMENEP - Abrori, Faizul; Syahril (SEKOLAH TINGGI ILMU SYARIAH ABU ZAIRI BONDOWOSO, 2022)
Islamic banking is very different in its application to conventional banking which uses interest, and Islamic banking is based on profit-sharing financing which is developed through musyarakah and mudharabah financing products. Thus, Islamic banking should have a positive impact on the real growth sector during the Covid-19 period that hit all corners of the country, including Sumenep Regency. One of the business units that need to be developed to encourage growth in the real sector is micro, small and medium enterprises (UMKM) which in the current national economy have a very important position. Many people have high hopes for Islamic banking in developing UMKM during the Covid-19 period. The purpose of this study was to find out the development of UMKM during the Covid-19 period through Islamic banking in Sumenep Regency. Qualitative research method by making a systematic, factual and accurate description of the development of MSMEs in the Covid-19 era through Islamic banking in Sumenep Regency, by observing, direct and in-depth interviews and documenting. key informants Director of BPRS Bhakti Sumekar and Supporting Informants are sharia banking practitioners, UMKM actors and community leaders, informants based on research objectives and certain considerations. Based on POJK No. 11/POJK.03/2020. 10 roles played by BPRS Bhakti Sumekar during the Covid-19 period in developing MSMEs in Sumenep Regency, BPRS Bhakti Sumekar is more sensitive to MSMEs which are customers or partners even though during the Covid-19 pandemic they still serve financing for MSME actors and relaxation of financing for MSMEs in Sumenep Regency and planning a Low Profit Sharing Financing Program in 2021.